Design of a robotic wrist rehabilitator - Lim, Yi Qun. (2010)
Stroke is one of the leading causes of disability and death in the world. Patients that suffered from minor stroke lapses undergo wrist rehabilitation and slowly regain their basic wrist movement through sessions of progressive wrist therapy. This project concerns the design and development of a robotic wrist rehabilitator. Study of the anatomy of the human wrist joint and wrist motion gives a better understanding on the design requirements of a wrist rehabilitation device. The mechanical design and functions of an existing wrist rehabilitation device is then analyzed. The pros and cons of the device are identified so that an improved version is created. The proposed prototype uses a cable-driven mechanism to achieve the pitch (flexion, extension) and yaw motion (abduction, adduction) of the wrist. The roll motion (pronation, supination) is provided separately by an external unit via a coupling when needed. Fabrication and assembly of the prototype is done and tests are carried out on the prototype to verify its functionality and performance. An important design consideration is to minimise the load on the patient’s wrist when using the device. This can be achieved by using light weight material for the handle and making its centre of mass close the wrist joint, reducing the torque loading. During testing, it is shown that the rehabilitator is able to provide the required range of motion for the human wrist. Conclusions and recommendations are included in the report.